PENGARUH MUTU PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP RSU. BUNDA THAMRIN MEDAN TAHUN 2012 - citra Triwahyuni (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT Service given by doctor and nurses is one of the factors deciding on the quality of hospital services. The type of this research was an explanatory research which was aimed to explain the influence quality of service on the level of satisfaction of the in-patients in Bunda Thamrin Hospital in 2012. The population were 420 in-patients on March. The sample were 81 respondent and determined by using accidental sampling. The data were colected by using questionnaires and analyzed by using multiple linear regression tests with the level of reliability of α = 0.05. The result of the research showed that the variables which had significant influence on the inpatients satisfaction was the doctors, service quality (p = 0.000). The variables which had not influence on the in-patients, the management’s service quality (p=0.467), satisfaction were the service quality of the nurse (p = 0,584), the service quality of serving food and nutrition (0,105), the service quality of medical support (p = 0,243), and the quality of environment (p = 0,737).It was suggested to the management of the Bunda Thamrin Hospital increased the quality of the doctor services to the patients